Deconstructing the Textual Representation of the Fathers in the Fantasy Picturebook One Dad, Two Dads, Brown Dad, Blue Dads (1994) - Martínez Lirola, María (Miscelánea: A Journal of English and American Studies, 2021)
This paper aims to explore the linguistic and visual choices used by the writer and the illustrator in order to create meaning in the fantasy picturebook One Dad, Two Dads, Brown Dad, Blue Dads (1994), written by Johnny Valentine and illustrated by Melody Sarecky, which features a gay family. The analytical tools employed in this study to deconstruct meanings in the said picturebook are Kress and van Leeuwen’s (2006) Visual Social Semiotics and Painter et al.’s (2013) model to read visual narratives in children’s picturebooks. The analysis concentrates on the textual and compositional metafunctions in order to observe the intersemiotic relationship between verbal and visual meanings and their realizations through various linguistic and visual modes. The methodology is qualitative-descriptive. One Dad, Two Dads, Brown Dad, Blue Dads reveals that both visuals and written text narrate the story, although it is the visual that is given a predominant role on the page due to its size, the location of the characters and the frames. The analysis shows that this is a picturebook in which having two fathers is represented as nonnormalized, although they perform their family duties as they are expected to because they do the same things that other fathers do.